LONG-CHAIN POLYUNSATURATED ω-3 AND ω-6 FATTY ACIDS AS ESSENTIAL NUTRIENTS IN DIFFERENT PERIODS OF CHILDHOOD - S. G. Makarova; E. A. Vishneva (Педиатрическая фармакология)
The authors present modern data on the issue of rational nutrition of children in different periods of childhood. The most frequent types of disorders are listed; insufficient consumption of long-chain polyunsaturated fatty acids is among them. The authors show that this issue is topical not only in Russia, but also in a range of the developed countries. The authors give special attention to classification and biological role of polyunsaturated fatty acids, especially in the development of nervous and immune systems. The authors demonstrated importance of sufficient consumption of long-chain polyunsaturated fatty acids in the period of fetal development for antenatal prevention of atopic disease. The authors list methods of recovery from deficiency of polyunsaturated fatty acids in antenatal and neonatal periods and after the first year of life.